Pengaruh pemberian pakan tambahan tepung Kiapu (Pistia stratiotes) dicampur dengan pakan komersil terhadap pertumbuhan benih ikan Lele Dumbo (Clarias gariepinus) - Irawadi Gunawan; Ummi Suraya (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2019)
This study aims to develop alternatives for making vegetable protein based feed for the growth of African Catfish seeds (Clarias gariepinus) by utilizing flour made from Kiapu (Pistia stratiotes). This research was conducted for ± 1 month, namely from September to October 2017. The place of this research was conducted at the Laboratory of Aquaculture Study Program, Department of Fisheries, Faculty of Agriculture, University of Palangka Raya. From the research that has been carried out it can be concluded that the growth rate of length and weight of African Catfish seeds during the observations showed good results. The use of kiapu flour as an addition to the Prima Feed commercial feed on the growth of African Catfish seeds shows a response to weight and length growth. However, for Fengli Fl-1 type feed, kiapu flour which is given in conjunction with Prima Feed type feed is still under Fengli Fl-1 type feed. Conversion of feed from Fengli Fl-1 commercial feed is lower than Prima Feed commercial feed mixed with kiapu flour. Keywords : Additional feed, kiapu flour, African Catfish seeds.